Manganese in Health and Disease 2014
DOI: 10.1039/9781782622383-00604
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Induced by Manganese

Abstract: This chapter summarizes the current studies on the genotoxic potential of manganese (Mn) and is thereby points out that the knowledge gained up to now is quite equivocal. Besides reviewing the current literature on Mn-induced DNA damage on a chromosomal as well as a DNA level, possible underlying mechanisms, including disturbances of DNA replication/DNA polymerases as well as DNA damage response pathways, are discussed. Finally, this chapter gives a brief overview of the possible consequences of DNA damage ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…These findings of decreased genomic integrity (increase of DNA strand breaks and oxidatively modified DNA bases) caused by Mn are in line with studies performed in neuroblastoma cells (SH-SY5Y) [57] and further corroborate the results of Yang et al [58], which show that Mn induces increased levels of 8OHdG in the striatum of mice. Other investigations in mammals and (neuronal) cell lines come to the same conclusion [24,41], but studies performed by Sava et al and Oikawa et al suggested that Mn causes an increase of 8oxodG levels of neuronal cells (PK-12), but only if co-incubated with dopamine or melanin [59,60]. Another in vitro study was performed on Mn-toxicity resistant cells (SCOV-3 clones) and showed that these cells have an increased ability of DNA repair, by means of enhanced PARP and AP endonuclease activity compared to the non-resistant original cell line.…”
Section: Mn Causes a Decrease In Genomic Integrity And The Formation Of Oxidative Dna Damage At Sub-toxic And Toxic Concentrationssupporting
confidence: 60%
See 1 more Smart Citation
“…These findings of decreased genomic integrity (increase of DNA strand breaks and oxidatively modified DNA bases) caused by Mn are in line with studies performed in neuroblastoma cells (SH-SY5Y) [57] and further corroborate the results of Yang et al [58], which show that Mn induces increased levels of 8OHdG in the striatum of mice. Other investigations in mammals and (neuronal) cell lines come to the same conclusion [24,41], but studies performed by Sava et al and Oikawa et al suggested that Mn causes an increase of 8oxodG levels of neuronal cells (PK-12), but only if co-incubated with dopamine or melanin [59,60]. Another in vitro study was performed on Mn-toxicity resistant cells (SCOV-3 clones) and showed that these cells have an increased ability of DNA repair, by means of enhanced PARP and AP endonuclease activity compared to the non-resistant original cell line.…”
Section: Mn Causes a Decrease In Genomic Integrity And The Formation Of Oxidative Dna Damage At Sub-toxic And Toxic Concentrationssupporting
confidence: 60%
“…Excessive production of reactive oxygen and nitrogen species (RONS), either directly via a Fenton-like reaction or indirectly by inhibiting the respiratory chain in mitochondria, leads to increased interactions with macromolecules such as DNA [23]. Recent evidence from in vitro studies suggests that Mn may damage the DNA or disturb cellular DNA damage response pathways under conditions of either overload due to high exposure or disturbed homeostasis [24]. The resulting DNA damage in combination with an insufficient DNA repair system might contribute to the neurological dysfunction [25,26].…”
Section: Introductionmentioning
confidence: 99%